Kualitas Pengungkapan Pelaporan Segmen pada Industri Manufaktur di Indonesia: Tinjauan Literatur Sistematis - Catherine Wijaya; Charen Patricia Sihotang; Corrie Yemima Ilona; Cristin Rosa Gultom; Samantha Sundari Wijaya; Rifani Akbar Sulbahri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to review and analyze the quality of segment reporting in the Indonesian manufacturing industry. As companies diversify their businesses, their operational structures become more complex, making consolidated financial statements less informative for investors. This research uses the Systematic Literature Review (SLR) method with the PRISMA protocol to analyze six key journals published between 2016 and 2026. The results show that the quality of segment disclosure is significantly influenced by company size and the reputation of "Big Four" public accounting firms. The findings also indicate that although operational diversification can increase the risk of earnings management, high-quality segment disclosure can actually improve earnings quality and help analysts predict future profits more accurately. Furthermore, using a reputable auditor is proven effective in reducing audit delay for companies with many segments. Overall, transparent segment reporting is a vital tool for investors to evaluate profitability when making investment decisions.